Grenada : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
The Grenadian economy began to recover owing to progress in a number of reforms, combined with prudent macroeconomic policies that helped boost private sector confidence. Despite these major strides, indices of poverty and unemployment are the highest in the Caribbean region. Revitalizing the agricultural sector is essential for a sustained recovery. Continued vigilance over the domestic banking system is needed. The IMF staff commends the government for maintaining an agenda of ambitious reforms. Although the statistical base has improved in recent years, weaknesses remain.